2015
DOI: 10.1007/s00442-015-3464-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and taxonomic controls on incorporation of microbial carbon and phosphorus by detritivorous caddisflies

Abstract: Heterotrophic microbes on detritus play critical roles in the nutrition of detritivorous animals, yet few studies have examined factors controlling the acquisition of microbial nutrients toward detritivore growth, which is termed “incorporation". Here, we assessed effects of detrital substrate identity (leaf type), background nutrients, and detritivore species identity on detritivore incorporation of microbial carbon (C) and phosphorus (P) in leaf litter diets. We fed oak and maple litter conditioned under two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…A meta-analysis found that detritivores tended to have a lower C GGE than herbivores (Frost et al, 2006), but other element-specific GGEs and AEs were not commonly available across feeding guilds, and it remains unclear how efficiently detritivores assimilate and convert nutrients into new growth. However, recent estimates for aquatic detritivore element-specific AEs and GGEs (Halvorson et al, 2015b, 2016b) suggest that N- and P-specific AE and GGE are lower than those estimated for aquatic herbivores (DeMott et al, 1998; Ferrão-Filho et al, 2007). Therefore, detritivores will likely excrete elements at lower and egest at higher rates than taxa in other feeding guilds (McManamay et al, 2011).…”
Section: Literature Review – Comparing Ecological Stoichiometry Of Grmentioning
confidence: 85%
See 3 more Smart Citations
“…A meta-analysis found that detritivores tended to have a lower C GGE than herbivores (Frost et al, 2006), but other element-specific GGEs and AEs were not commonly available across feeding guilds, and it remains unclear how efficiently detritivores assimilate and convert nutrients into new growth. However, recent estimates for aquatic detritivore element-specific AEs and GGEs (Halvorson et al, 2015b, 2016b) suggest that N- and P-specific AE and GGE are lower than those estimated for aquatic herbivores (DeMott et al, 1998; Ferrão-Filho et al, 2007). Therefore, detritivores will likely excrete elements at lower and egest at higher rates than taxa in other feeding guilds (McManamay et al, 2011).…”
Section: Literature Review – Comparing Ecological Stoichiometry Of Grmentioning
confidence: 85%
“…Given the importance of microbial C in supporting detritivore growth (Chung and Suberkropp, 2009a; Halvorson et al, 2016b), it is difficult to determine whether positive growth effect sizes are driven by elevated dietary microbial biomass or increased N and P availability. However, one feeding study explicitly manipulated detrital P content without changing fungal biomass and still found strong P-limitation of growth, suggesting P can limit detritivore growth, independent of microbial biomass (Danger et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In streams, litter inputs are immediately colonised by microbes, resulting in net nutrient removal (hereafter uptake) from stream water (Mulholland, 2004). These processes of C and nutrient uptake and release often Correspondence: Halvor M. Halvorson, 601 Science Engineering Fayetteville, AR 72701, U.S.A. E-mail: halvorso@gmail.com regulate ecosystem elemental cycles in low-order forested streams (Mulholland, 2004) and form a link among detrital energy, dissolved nutrients and consumer growth (Cummins, 1973;B€ arlocher, 1985;Halvorson et al, 2016). These processes of C and nutrient uptake and release often Correspondence: Halvor M. Halvorson, 601 Science Engineering Fayetteville, AR 72701, U.S.A. E-mail: halvorso@gmail.com regulate ecosystem elemental cycles in low-order forested streams (Mulholland, 2004) and form a link among detrital energy, dissolved nutrients and consumer growth (Cummins, 1973;B€ arlocher, 1985;Halvorson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%